2012
DOI: 10.1091/mbc.e11-05-0412
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein QKI5 is a direct target of C/EBPα and delays macrophage differentiation

Abstract: Differentiated macrophages are essential for the innate immune system; however, the molecular mechanisms underlying the generation of macrophages remain largely unknown. Here we show that the RNA-binding protein QKI, mainly QKI-5, is transcriptionally activated in the early differentiated monocytic progenitors when CCAAT/enhancer-binding protein (C/EBP) α is expressed. The forced expression of C/EBPα increases the endogenous expression of QKI. Chromatin immunoprecipitation analysis and reporter assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…This observation was consistent with previous published studies involving miR-29a and QKI [11,21]. On further analysis, it was identified that QKI has mir-29a binding sites in 3 0 UTR of its mRNA.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This observation was consistent with previous published studies involving miR-29a and QKI [11,21]. On further analysis, it was identified that QKI has mir-29a binding sites in 3 0 UTR of its mRNA.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we have tried to elucidate a novel mechanism that regulates SRA expression. Based on the previously published studies by us and other labs, it has been shown that during monocyte differentiation into macrophages, a) QKI expression is inhibited [11,5], and, b) miR-29a enhanced SRA expression [5,18]. So, this led us to ask a question, how miR-29a is regulating SRA expression and is it possible that these three genes are inter-related in terms of their regulation of each other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In adult mammals, qki mRNAs can be detected in tissues, such as the heart, skeletal, lung, testes and immune cells in addition to the central nervous system (CNS) (9,(12)(13)(14)(15). In a search for putative RNA targets recognized by QKI, a bipartite consensus sequence ACUAAY-N(1-20)-UAAY was defined as a QKI response element (QRE), and 1,430 putative mRNA targets were identified by bioinformatic analysis (16).…”
Section: Introductionmentioning
confidence: 99%